Framework for optimisation of the clinical use of colistin and polymyxin B: the Prato polymyxin consensus. Issue 2 (February 2015) - Nation, Roger L; Li, Jian; Cars, Otto; Couet, William; Dudley, Michael N; Kaye, Keith S; Mouton, Johan W; Paterson, David L; Tam, Vincent H; Theuretzbacher, Ursula; Tsuji, Brian T; Turnidge, John D
Summary In the face of diminishing therapeutic options for the treatment of infections caused by multidrug-resistant, Gram-negative bacteria, clinicians are increasingly using colistin and polymyxin B. These antibiotics became available clinically in the 1950s, when understanding of antimicrobial pharmacology and regulatory requirements for approval of drugs was substantially less than today. At the 1st International Conference on Polymyxins in Prato, Italy, 2013, participants discussed a set of key objectives that were developed to explore the factors affecting the safe and effective use of polymyxins, identify the gaps in knowledge, and set priorities for future research. Participants identified several factors that affect the optimum use of polymyxins, including: confusion caused by several different conventions used to describe doses of colistin; an absence of appropriate pharmacopoeial standards for polymyxins; outdated and diverse product information; and uncertainties about susceptibility testing and breakpoints. High-priority areas for research included: better definition of the effectiveness of polymyxin-based combination therapy compared with monotherapy via well designed, randomised controlled trials; examination of the relative merits of colistin versus polymyxin B for various types of infection; investigation of pharmacokinetics in special patient populations; and definition of the role of nebulised polymyxins alone or in combination with intravenous polymyxins for the treatment of pneumonia. The key areas identified provide a roadmap for action regarding the continued use of polymyxins, and are intended to help with the effective and safe use of these important, last-line antibiotics.